Traumatic pseudoaneurysm of the facial artery: Underrecognized vascular entity - Zahra Sayad, MD; Mohammed Abid, MD; Nejwa Belhaj, MD (Radiology Case Reports)
Facial artery pseudoaneurysm, although rare, is a serious condition caused by rupture of artery with extravasation of blood. The compressed perivascular tissue forms the wall of aneurysmal sac, typically presents as a pulsatile swelling. Diagnosis is confirmed through computed tomography (CT), angiography, or ultrasound. Treatment options vary depending on the size and symptoms and include observation, compression, surgical resection, vessel ligation, embolization, and intralesional sclerotherapy. A 42-year-old male with no significant past medical history, presented with a painless, pulsatile, firm mass measuring 2 × 1.5 cm in the left jugal peribuccal region that had progressively grown over 2 months. Ultrasound and computed tomography imaging revealed a pseudoaneurysm of facial artery. Under local anesthesia and intravenous sedation, we performed a surgical resection of the mass with ligation of the vessels, highlighting the importance of early diagnosis and appropriate surgical intervention.